Nano-characterisation of dielectric breakdown in the various advanced gate stack MOSFETs. (6th June 2007) - Pey, K.L.; Tung, C.H.; Ranjan, R.; Lo, V.L.; MacKenzie, M.; Craven, A.J.
Nano-scale physical analysis of breakdown in nano-scale high-κ gate stacks consisting of either polycrystalline-silicon or metal as gate electrode shows that the microstructural defects and damages induced by breakdown in the high-κ gate dielectric are different from that of conventional SiOxNy/poly-Si and Si3N4/poly-Si gate stacks. Chemical analysis using transmission electron microscopy provides useful information about the nature and evolution of the breakdown induced defects in different gate stacks metal-oxide-semiconductor field effect transistors. Together with electrical characterisation, the possible gate leakage conduction mechanism(s) in various dielectric breakdown has been established. This paper reviews the breakdown conduction mechanism(s) and induced defects in high-κ gate stacks in comparison to conventional gate dielectrics. The impacts of the new failure mechanisms on the performance and reliability of various gate stacks are discussed.